Leptin does not respond to 48 h fat deposition or mobilization in women. - Murgatroyd, P; Frühbeck, G; Goldberg, G; Jebb, SA; Leahy, F; Moore, MS; Prentice, A (2003)
OBJECTIVE: To test the hypothesis that acute responses of plasma leptin concentration to energy balance manipulation are mediated by fat flux. DESIGN: Ten healthy women aged 31-63 y, mass 48-113.5 kg, fat mass 8.5-62.5 kg, were studied for 3 days in a whole-body calorimeter on two occasions. After a control day (D1) during which energy balance was maintained, diet was manipulated to induce fat deposition (FD) or mobilization (FM) of 50 g/day for 2 days (D2 and D3). A difference totalling of 194+/-18.6 g fat was achieved between manipulations without significant effects on carbohydrate or protein balance. Fasting plasma leptin was measured on D2 and D4. RESULTS: After the control day plasma leptin concentration averaged 19.01+/-9.8 ng/ml, and was found to be linearly related to body fat mass. After 2 days manipulation of fat balance, leptin concentrations were 21.4+/-10.3 ng/ml (FD) and 21.2+/-11.3 ng/ml (FM). There was no significant difference between treatments in either control day or postmanipulation leptin concentrations, nor did the treatments induce any differences in glucose or insulin concentration responses. CONCLUSION: Although in states of energy balance leptin concentration is linearly related to fat mass, acute modulation of leptin concentration during energy imbalance is not mediated by fat flux.